Synthesis of Immunoglobulin Heavy and Light Chains by the Free Ribosomes of a Mouse Plasma Cell Tumor - Lisowska-Bernstein, B. (1970)
Free and membrane-bound ribosomes have been isolated from a mouse plasma cell tumor secreting immunoglobulins, and allowed to synthesize proteins under cell-free conditions. Analysis of the products of synthesis by autoradiography of immunoelectrophoresis and peptide maps indicates that both types of ribosomes synthesize heavy and light immunoglobulin chains.